Actinomyces odontolyticus causing meningitis and cervical abscess. Issue 4 (4th July 2021) - Jain, Hanish; Singh, Garima; Eranki, Ambika
Abstract: Actinomyces spp. are filamentous gram-positive bacilli found in humans as a common flora of the oropharynx, gastrointestinal tract, and urogenital tract. Actinobacteria are normally present in the gums and are a common cause of infection in dental procedures and oral abscesses. To date, no cases of A. odontolyticus causing meningitis and cervical abscess have been reported in online databases. Therefore, we report the first case of A. odontolyticus meningitis and recurrent cervical abscess due to translocation from the oral cavity.